Housing choices in later life as unclaimed forms of housing activism. Issue 1 (3rd April 2017) - Jones, Andrea
ABSTRACT: This paper explores how housing choices over a lifetime produce under-recognised and unclaimed forms of housing activism. It is based on qualitative interviews with two individuals in their sixties, living in intergenerational communities in the South of England. I argue that their stories of their housing choices and their future housing plans resist dominant housing discourses, particularly as they relate to ageing, and they illuminate a number of under-recognised elements of housing activism. Using Clapham's housing pathway concept, I describe their narratives of decision-making about where and how to live over their life time to show their agency and their resistance to norms of housing consumption in later life, which are key elements of housing activism. Whilst interviewees recognised the political nature of their housing choices, neither claimed the term 'housing activist' nor used the term in their narratives and I argue that this may be because their forms of housing activism were interwoven with domestic and caring needs, emotional experiences, intermittent commitment and ageing identities. Their housing pathways and life stories support emerging theories of activism that broaden definitions from public to private spaces and challenge stereotypes of older people's involvement in housing activism.